Effect of Concentration of Entomopathogenic Nematodes (Steinernema spp.) to Bemisia tabaci Genn. (Hemiptera; Aleyrodidae) On Red Chili Plants - Toto - Sunarto; Fahira Endaningsih Pubarianto (Departemen Hama dan Penyakit Tumbuhan Fakultas Pertanian Universitas Padjadjaran, 2021)
Bemisia tabaci is an important pest on red chili plants. The entomopathogenic nematodes Steinernema spp. has the potential to control insect pest populations. The purpose of this study was to obtain the concentration of Steinernema spp. the most effective in controlling B. tabaci on red chili plants. The experiment was conducted at the Greenhouse, Faculty of Agriculture, Universitas Padjadjaran, Jatinangor, from January to September 2020. The study used experimental methods in-vitro and in-vivo. The in-vitro experiment used a completely randomized design to observe the mortality of B. tabaci. The in-vivo experiment used a Randomized Block Design to observe the population of B. tabaci. The experiment consisted of seven treatments and four replications. The treatments consisted of: control (without Steinernema spp.), 50, 100, 150, 200, 250, and 300 IJ/ml (IJ = third infective juvenile). Each treatment was infested with 20 second nymphs B. tabaci and using red chili plants 30 days after planting. The results showed that the entomopathogenic nematode Steinernema spp. at a concentration of 300 IJ/ml, the most effective in causing mortality of B. Tabaci and at concentration of 100 IJ/ml can suppress B. tabaci population on chilli plant at lower level in 12 days after application.